Submandibular swelling, pulsations and otalgia due to sublingual gland and blood vessels herniation through mylohyoid boutonnière: Case report - Janović Aleksa; Bracanović Đurđa; Antić Svetlana; Marković-Vasiljković Biljana (Balkan Journal of Dental Medicine, 2022)
Background/Aim: Mylohyoid boutonnière is a common anatomical variant with extremely rare clinical manifestations. We report two cases of symptomatic unilateral mylohyoid boutonnière with sublingual gland herniation. Case report: The first was a 34-year-old female with a two months history of a left submandibular swelling, intermittent pulsations, and otalgia. The second 67-year-old female presented with a left submandibular pain six months after total thyroidectomy due to papillary carcinoma. After detailed clinical and radiological evaluation by ultrasonography (US) and computed tomography (CT), the mylohyoid gap with sublingual gland herniation was diagnosed in both patients. The dynamic US with a tongue pressed down on the mouth floor revealed blood vessel compression by a herniated sublingual gland in the first patient. Conclusions: This is the first case of a mylohyoid boutonnière related intermittent vascular compression. Dynamic US and CT may help to differentiate intermittent and persistent sublingual gland herniation through the mylohyoid boutonnière from other pathological lesions in the submandibular region.